The potential of phosphate solubilizing microorganisms (PSM) isolated from different ecosystems on calcareous soils in Timor Island, Indonesia - Adu Tae, Anthonius S. J.; Nur, Mahmuddin S.M.; Benggu , Yoke Ivonny; Ishaq, Lily F.; Soetedjo, I N. Prijo; Widinugraheni, Sri; Kasim, Muhammad (Journal of Degraded and Mining Lands Management, 2025)
The study was conducted in three different ecosystems: mamar (a typical local ecosystem close to water catchment areas), farm, and coastal ecosystems. In each ecosystem, soil samples were taken from the rhizosphere of five different plants to investigate the occurrence of PSM, molecularly identify the potential isolates, and evaluate their ability to increase soil phosphorus (P) availability and mungbean yield. The highest population of phosphate-solubilizing bacteria (PSB) was found in the mamar ecosystem. Phosphate-solubilizing fungi were only found in the farm and coastal ecosystems, with low populations, and restricted to the rhizosphere of a few plants. The number of PSB isolates was higher in the coastal ecosystem, followed by the farm and mamar ecosystems. The phosphate solubilizing index of the isolate was quite high, ranging from 210 to 300. One isolate from the five molecularly selected isolates from Kupang regency was identified as Aspergillus sp. (cassava rhizosphere origin), one isolate from the farm ecosystem (Moringa rhizosphere origin), and three isolates from the coastal ecosystem (Jatropha gossypiifolioa, Scheichera oleosa and Calotropis gigantea L. rhizosphere origin) were all identified as Pseudomonas sp. Two selected isolates from a previous study in Timor Tengah Selatan regency, collected from the mamar ecosystem (bamboo and Leuchaena leucocephala rhizosphere), were both identified as Acinetobacter baumannii. Inoculation of PSB resulted in higher available soil P compared to the uninoculated treatment. PSB inoculation also provided higher tissue P than the uninoculated treatment. PSB from coastal areas gave the highest pod weight and seed weight compared to other inoculation treatments.